Social Support and Self Efficacy Islamic Students in Online Learning - Melisa Paulina (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2023)
During the online learning period there are obstacles and obstacles faced by students, even so learning must still be carried out, so students are expected to be able to convince themselves to be able to achieve online learning goals. The purpose of this study was to determine the effect of social support on selfefficacy in Islamic students. This study used a quantitative approach with a sample of 410 students, with 124 male students and 286 female students. The general self-efficacy scale-12 (GSES-12) developed by Bosscher & Smit (1998) is used by researchers to measure self-efficacy, and the multidimensional scale of perceived social support (MSPSS) created by Zimet et al. (1988) researchers used to measure social support. Test the validity of the construct measurement on each variable was carried out after data collection and before data analysis. In testing the validity of measuring instruments, researchers used confirmatory factor analysis (CFA) (Muthen & Muthen, 2017). Hypothesis testing was carried out using the software SPSS Version 24. The results showed a significance value of .000 (p < .05) thus, there was a significant influence between social support on the self-efficacy of Islamic students in online learning. The results of the regression analysis test obtained an R Square of .152 or 15.2% on the effect of social support on self-efficacy in Islamic students in online learning.